Snow Characteristics along Caribou Trails and within Feeding Areas during Spring Migration - Duquette, Lauren S. (ARCTIC, 1988)
Snow depth and hardness were measured at caribou feeding sites and along migration trails during spring migration of the Porcupine Caribou Herd from NE Alaska to Yukon. Snow was deeper along migration trails than within adjacent feeding areas, while no distinction was evident with respect to snow hardness between feeding and trailing areas. Average snow depths and hardness indexes were at or below values identified by previous authors as critical upper limits to caribou activity.Key words: caribou, migration, winter, spring, snow, foraging, behaviour, Porcupine Caribou Herd Mots clés: caribou, migration, hiver, printemps, neige, broutement, comportement, la herde Porcupine